2020
DOI: 10.3390/vetsci7010007
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Vaccination Routes against Paratuberculosis Modulate Local Immune Response and Interference with Tuberculosis Diagnosis in Laboratory Animal Models

Abstract: Paratuberculosis (PTB) is an enteric granulomatous disease caused by Mycobacterium avium subsp. paratuberculosis (MAP) that mainly affects ruminants. Current vaccines have shown to be cost–effective control reagents, although they are restricted due to cross-interference with bovine tuberculosis (bTB). Therefore, novel vaccination strategies are needed and this study is focused on evaluating alternative vaccination routes and their effect on the local immune response. The MAP oral challenge rabbit model was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
8
2
Order By: Relevance
“…The subclinical nature of the infection model is probably contributing to this fact. CV showed the highest lymphoproliferative expression in comparison to the oral vaccines probably due to the administration route and the persistence of the granuloma generated at the injection site, which has shown to correlate in size to anti-PPA3 antibody levels in the previous works 19 .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The subclinical nature of the infection model is probably contributing to this fact. CV showed the highest lymphoproliferative expression in comparison to the oral vaccines probably due to the administration route and the persistence of the granuloma generated at the injection site, which has shown to correlate in size to anti-PPA3 antibody levels in the previous works 19 .…”
Section: Discussionmentioning
confidence: 64%
“…Besides, these vaccines present some negative aspects to overcome, such as, some interference with bTB diagnostic tests 15 . This problem may be solved by changing the vaccination route from subcutaneous to oral 19 , though mucosal immunity activation through this route must be tested. In our study we have shown that mucosal activation is possible through oral vaccination (even with inactivated vaccines), and that vaccination against PTB with experimental vaccines (Map inactivated and C. pseudotuberculosis inactivated) and with a Map commercial vaccine is able to enhance neutrophil functionality (showing trained immunity effects) as seen by increased phagocytosis and ET release, important mechanisms for bacterial clearance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations